Hardware and software complex for studying conductivity and capacitance of black lipid membranes - Berest, V. P.; Arenkin, P. V. (Biophysical Bulletin, 2009)
Measurement of electrophysiological parameters of black lipid membranes modified with proteins or peptides allows establishing the mechanisms of ion transport in biological membranes at the level of single molecules. This paper describes the developed prototype of an experimental setup for studying the conductivity and capacity of the modified black lipid membranes. The prototype represents a microcontroller system of data management and acquisition, executed in a modern analog and digital element base. The software is implemented in assembler for the microcontroller of PIC18F4xx family and debugged in MPLAB IDE integrated development environment.